Symptomatic dry eye disease and associated factors among postgraduate students at Hawassa University, Sidama Region, Ethiopia - Mikias Mered Tilahun; Henok Biruk Alemayehu; Biruk Lelisa Eticha; Getasew Alemu Mersha; Melkamu Temeselew Tegegn; Tarekegn Cheklie Zeleke; Nardos Hussen Abdulkadir; Abdisa Gemedi Jara; Ermias Solomon Yalew; Kalkidan Berhane Tsegaye; Merkineh Markos Lorato (Scientific Reports)
Abstract Dry eye disease and its symptoms are becoming an increasingly significant public health issue. This study aims to understand the extent of the disease, particularly in light of the post-COVID digital revolution. Specifically, it investigates the prevalence of symptomatic dry eye and its associated factors among postgraduate students at Hawassa University in the Sidama region of Ethiopia.A cross-sectional institutional study was conducted involving 442 postgraduate students selected through simple random sampling. Data collection included administering an online questionnaire that assessed sociodemographic, behavioral, and clinical factors and the ocular surface disease index. Of all students, 438 completed the study, resulting in a 99% response rate. The prevalence of symptomatic dry eye disease among the postgraduates was 44.5% (95% CI: 40 − 49.3%). Being female (AOR: 1.19, 95%CI1.18–3.11, P = 0.009), usage of a visual display unit for more than eight years (AOR: 3.12, 95% CI 1.66–5.85, P = 0.04), and history of allergic conjunctivitis (AOR: 6.89, 95% CI 3.37–14.08, P < 0.001) were significantly associated with symptomatic dry eye disease. A significant number of participants were found to have symptomatic dry eye disease. Therefore, it is recommended that educational programs, short-term training, and refresher courses be considered at Ethiopian universities.